1994
DOI: 10.1111/j.1432-1033.1994.tb19914.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock enhances the amount of prenylated Dnaj protein at membranes of glyoxysomes

Abstract: Proteins similar to the bacterial Dnaj protein have been implicated as molecular chaperones in different compartments of eukaryots. A plant equivalent is now described in tissues of dark-grown cucumber seedlings. Using a cucumber Dnaj protein produced by expression in bacteria, we raised polyclonal antibodies against the protein and used them for localization studies. In etiolated cucumber seedlings, both cotyledons and hypocotyledons were found to contain Dnaj proteins. Cell fractionation of etiolated cotyled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 42 publications
0
21
1
Order By: Relevance
“…Chaperones Hsp70 and Hsp90 were among the proteins identified whose expression is up-regulated during the heat shock response (39). Hsp70 and Hsp40 have been localized to peroxisomal membranes (27)(28)(29), and the amount of Hsp40 associated with these membranes increases after heat stress (28). An Hsp70 has also recently been identified in the matrix of watermelon glyoxysomes (50).…”
Section: Heat Shock Leads To Increased Peroxisomal Proteinmentioning
confidence: 99%
See 3 more Smart Citations
“…Chaperones Hsp70 and Hsp90 were among the proteins identified whose expression is up-regulated during the heat shock response (39). Hsp70 and Hsp40 have been localized to peroxisomal membranes (27)(28)(29), and the amount of Hsp40 associated with these membranes increases after heat stress (28). An Hsp70 has also recently been identified in the matrix of watermelon glyoxysomes (50).…”
Section: Heat Shock Leads To Increased Peroxisomal Proteinmentioning
confidence: 99%
“…Many researchers have reported that the folding state of peroxisomal proteins is not critical for membrane translocation (30 -34). On the other hand, chaperones, which are known to control protein folding reactions, have been implicated in peroxisomal protein import (27)(28)(29). To resolve this apparent conflict, we examined the participation of Hsps in protein import, the interactions between cytoplasmic Hsps and peroxisomal proteins, and the effect of the assembly state of the targeted protein on import efficiency.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Alignment of the Chlamydomonas protein with the plant proteins shows that it contains an N-terminal extension of 19 amino acids enriched in methionine, glycine, phenylalanine, and proline. Like other Hsp40 proteins from plants, the Chlamydomonas Dnj1 protein contains a CAQQ motif at the C terminus (Frugis et al 1999;Nambara and McCourt 1999), suggesting that the protein may be post-translationally modified by prenylation as has been demonstrated for some plant DnaJ proteins (Preisig-Muller et al 1994) and for the S. cerevisiae Ydj1 protein (Caplan et al 1992). …”
mentioning
confidence: 98%